Novitates neocaledonicae VI: Acropogon mesophilus (Malvaceae, Sterculioideae), a rare and threatened new species from the mesic forest of New Caledonia - Munzinger, Jérôme; Gâteblé, Gildas (Phytotaxa, 2017)
A new species, Acropogon mesophilus Munzinger & Gâteblé (Malvaceae, Sterculioideae), is described from New Caledonia. This species is endemic to non-ultramafic areas, along the southwestern coast of Grande-Terre. The species has large leaves, widely ovate to ovate, and entire, and might be confused with only two other endemic species, namely A. bullatus (Pancher & Sebert) Morat and A. veillonii Morat. However, A. mesophilus differs from the other two species most evidently by its leaves 3-nerved, flat, and with truncate to rounded bases, versus leaves 5-nerved, bullate, and with cordate bases. A line drawing and color photos are provided for the new species, along with a discussion of its morphological affinities and a preliminary risk of extinction assessment of Endangered.